Article Review: Bpjs Patient's Satisfaction with Waiting TIme of Administrative And Pharmacy Services - Silvia Intan Wardani; Gusti Agung Sri Guntari (Babali Health, 2024)
Introduction: The waiting time for services is one of the aspects that is thought to affect patient satisfaction. In many hospitals, patients frequently complain about the length of the wait for services. The study aims to explore BPJS Patient's Satisfaction towards Waiting Time of Administrative and Pharmacy Services. Methods: The method used in this literature review is to examine the results of previous research in published articles. Article searches were carried out via PubMed, Science Direct and Google Scholar using the keywords using keyword were "BPJS patient's satisfaction", "administrative services", and "waiting time pharmacy". The inclusion criteria of this study were BPJS patient's satisfaction, published articles, Bahasa article, English articles, and full-text access. The study only focused on administrative services and waiting time pharmacy, all of the studies involved other conditions were removed. Data were extracted and recorded using a table consisting of author names, years, methods, instruments, and findings, including factors related to and variable dimensions. Result: The results of the study found that 15 articles based on satisfaction indicators, there were four dissatisfied journals (26.7%) and (73, 3%) satisfied with Waiting Time of Administrative and Pharmacy Services. Patient satisfaction will impact the quality of service in a hospital.